The Art of CRM Proven Strategies for Modern Customer Relationship Management. - Fatouretchi, Max (Packt Publishing, Limited, 2019)
Max Fatourechi shares his decades of experience building successful CRM systems that make a real difference to business performance. Through clear processes, actionable advice, and informative case studies, The Art of CRM teaches you to design successful CRM systems for your clients.